EFFECT OF AIR FLOW RATE ON AIR-LIFT- PUMP - Amat Agus Salim; Edi Susanto; Daru Sugati; Harianto (KURVATEK, 2022)
Airlift pump is a series of tools used to transport water and air cargo (muddy) from one place to another. The Airlift pump work system through the pipe media by injecting air into the channel under the submerged pipe. The air pressure from the aerator will push the air to move upward in the same direction through the pipe. Viscous liquids or sludge can be raised using an air-lift-pump. The buoyant force from the air can cause the heavy hydrostatic liquid to become smaller because the air used in the air-lift-pump is injected at the bottom of the pipe. This study used an experimental method by varying the air discharge ratio and using different air injectors. The purpose of this study was to determine the effect of variations in the injection discharge ratio on pump performance and to find the best efficiency for each variation made. The test was carried out with 3 different injector pipes (0.80 mm, 0.54 mm, 0.31 mm). The results showed that variations in the air discharge ratio greatly affect the efficiency and flow rate of water. The highest efficiency occurred in an injector with a diameter of 0.8 mm by 4.1% and the highest efficiency occurred in an injector with a diameter of 0.31 mm by 1.3%. Variation of air discharge with a greater value then the efficiency value will decrease. The water flow rate also changes because the greater the air discharge given, the greater the value of the water flow rate. Keywords : airlift pump, efficiency, variasi rasio debit udara, injector